Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1753193415622342
|View full text |Cite|
|
Sign up to set email alerts
|

Patients with triangular fibrocartilage complex injuries and distal radioulnar joint instability have reduced rotational torque in the forearm

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…2 Contrary to these results, Andersson et al showed in a more recent study that patients who had arthroscopic signs of TFCC also had a concomitant loss in strength in forearm rotation. 7 The difference between these two studies lies in the difference in duration from onset of symptoms until the torque strength test was done. It may be speculated that the long duration of 2 years from injury to test in Landau's patient group enabled compensatory muscle groups to get strong enough to create stability in the test situation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Contrary to these results, Andersson et al showed in a more recent study that patients who had arthroscopic signs of TFCC also had a concomitant loss in strength in forearm rotation. 7 The difference between these two studies lies in the difference in duration from onset of symptoms until the torque strength test was done. It may be speculated that the long duration of 2 years from injury to test in Landau's patient group enabled compensatory muscle groups to get strong enough to create stability in the test situation.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-and postoperative forearm peak pronation and supination torque measurements were performed using a wrist dynamometer supplied with a digital pressure gauge (Model BL-2000, Baseline, White Plains, New York) ( Figure 1). [4][5][6] The device was calibrated at the Research Institute of Sweden (RISE), division SP (Statens Provningsanstalt). The precision of measurement of the dynamometer was 0.01 Nm.…”
Section: Torque Measurementsmentioning
confidence: 99%
“…The protocol for measurement followed that of a recently published validity study 6 and the preoperative measurement of suspected TFCC 1B injuries by Andersson et al 4 The patient was in a standing position, fully adducted arm and elbow flexed to 90°. Peak supination followed by peak pro-nation torque were measured once starting from a neutral position, with the examiner carefully ensuring that the patient did not bring the elbow into abduction or lean the body in any direction.…”
Section: Torque Measurementsmentioning
confidence: 99%
See 2 more Smart Citations